Reasoning, emotions, and delusional conviction in psychosis. - Garety, P; Freeman, D; Jolley, S; Dunn, G; Bebbington, P; Fowler, D; Kuipers, E; Dudley, R (2005)
The aim of the study was to elucidate the factors contributing to the severity and persistence of delusional conviction. One hundred participants with current delusions, recruited for a treatment trial of psychological therapy (PRP trial), were assessed at baseline on measures of reasoning, emotions, and dimensions of delusional experience. Reasoning biases (belief inflexibility, jumping to conclusions, and extreme responding) were found to be present in one half of the sample. The hypothesis was confirmed that reasoning biases would be related to delusional conviction. There was evidence that belief inflexibility mediated the relationship between jumping to conclusions and delusional conviction. Emotional states were not associated with the reasoning processes investigated. Anxiety, but not depression, made an independent contribution to delusional conviction.